Trójwarstwowa struktura informacji w treści wypowiedzi1 (szkic o programie Gramatyki Rozproszonej) - Włodarczyk, André; Włodarczyk, Hélène (Investigationes Linguisticae, 2016)
The idea of the three-tier information structure in the content of utterances is the result of research carried out in a transdisciplinary spirit, within sciences such as linguistics, psychology, logic and computer science. The theory of Meta-Informative Centering (MIC) of attention, which borrows the concept of attention centering from psychology and the concept of information from computer science, makes it possible to treat ―information structures" or "thematic-rhematic structures" as strictly dependent on the canonical form of utterances (as the manifestation of predication). Thus, an important feature of the MIC theory is its reference to predication, and in particular to the language of classical logic (first-order predicate logic). In the light of MIC theory, "information structure" appears in fact to be a structure of meta-information (representing "information about information") with respect to orthoinformation (proper information; i.e. situation frame, its types and aspects, roles, spatio-temporal anchors etc.) contained in the utterances. It is the theory of Associative Semantics (AS), which is being developed in parallel to the theory of MIC, which constitutes the layer of ortho-information. However, the foundational role in the structure of information content of utterances is played by para-information ("information which is similar or related to some other information"). In order to treat systematically the structure of information (ortho-, meta- and para-information) as contained in language utterances, and for representing their fundamental components, we proposed using ―formal concepts‖ belonging to the rapidly developing new field of research in computer science under the general name of ―Formal Concept Analysis‖ (FCA). The most important operations (responsible for the structure of information contained in the body of the utterances) are as follows: (a) selection (for building conceptual areas of interest in the para-information tier), (b) configuration (for building relationships between concepts in the ortho-information tier) and (c) centering (secondary selection of concepts for transmitting in the meta-information tier), while the most important operations (responsible for the structure of utterances) are: (a) nesting (for building utterances as units of discourse in the profile, across the tiers) and (b) encapsulation (for designating the conceptual space and combining conceptual representations with the language). In this paper we present one of the many areas of application of the described theoretical foundation, namely: word order in linguistic typology. Research taking into account the abovementioned three kinds of information constitutes a contribution to the construction of a coherent theoretical framework for Distributed Grammar (i.e. multi-tier grammar with a generalized idiomatics).